Response of young patients with probable ICD-11 complex PTSD to treatment with developmentally adapted cognitive processing therapy. Issue 1 (1st January 2021) - Eilers, Rebekka; Rimane, Eline; Vogel, Anna; Renneberg, Babette; Steil, Regina; Rosner, Rita
ABSTRACT: Background : ICD-11 features Complex Posttraumatic Stress Disorder (CPTSD) as a new diagnosis. To date, very few studies have investigated CPTSD in young patients, and there is a need for evidence on effective treatment. Objective : The present study evaluates the applicability of developmentally adapted cognitive processing therapy (D-CPT) for CPTSD in young patients in a secondary analysis of the treatment condition of a randomized controlled trial (RCT) investigating the efficacy of D-CPT. Methods : The D-CPT treatment group in the original study included 44 patients (14–21 years) with DSM-IV PTSD after childhood abuse. We used the ICD-11 algorithm to divide the sample into a probable CPTSD and a non-CPTSD group. We performed multilevel models for interviewer-rated and self-rated PTSD symptoms with fixed effects of group (CPTSD, non-CPTSD) and time (up to 12 months follow-up) and their interaction. Treatment response rates for both groups were calculated. Results : Nineteen (43.2%) patients fulfilled criteria for probable ICD-11 CPTSD while 25 (56.8%) did not. Both CPTSD and non-CPTSD groups showed symptom reduction over time. The CPTSD group reported higher symptom severity before and after treatment. Linear improvement and treatment response rates were similar for both groups. D-CPT reduced symptoms of disturbances in self-regulation in both groups. Discussion : Both, patients with and without probable ICD-11 CPTSD seemed to benefit from D-CPT and the treatment also reduced disturbances in self-regulation. Conclusion : This study presents initial evidence of the applicability of D-CPT in clinical practice for young patients with CPTSD. It remains debatable whether CPTSD implies different treatment needs as opposed to PTSD. HIGHLIGHTS: We investigated the applicability of developmentally adapted cognitive processing therapy (D-CPT) to reduce PTSD symptoms in abused young patients with and without probable CPTSD. Findings showed significant reduction of PTSD symptoms in both groups and results remained stable over a 12-month follow-up period.